2017
DOI: 10.1016/j.brainres.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of a Radial Water Tread maze can distinguish cognitive deficits in mice with traumatic brain injury

Abstract: Introduction: The use of forced-swim, rat-validated cognition tests in mouse models of traumatic brain injury (TBI) raises methodological concerns; such models are vulnerable to a number of confounding factors including impaired motor function and stress-induced non-compliance (failure to swim). This study evaluated the ability of a Radial Water Tread (RWT) maze, designed specifically for mice, that requires no swimming to distinguish mice with controlled cortical impact (CCI) induced TBI and Sham controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…11 We used a 2-mm impact depth in this study, which we have previously shown to have a strong impact on learning and memory, and on striatum-mediated torsoflexion in the mice. 11 CCI mice also have acute impairments in other motor-mediated tasks, such as the rotarod test, and chronic impairments in tests of fine motor coordination, such as the beamwalk and gridwalk tests 10,18,19 ; however tests of locomotor ability and exploration in novel chambers show that the mice are not impaired in their ability to walk given that their locomotion distance in a novel arena remains similar to sham mice. 10 The literature surrounding the use of CatWalk as a tool to detect motor impairments after TBI has both negative and positive findings.…”
Section: Discussionmentioning
confidence: 99%
“…11 We used a 2-mm impact depth in this study, which we have previously shown to have a strong impact on learning and memory, and on striatum-mediated torsoflexion in the mice. 11 CCI mice also have acute impairments in other motor-mediated tasks, such as the rotarod test, and chronic impairments in tests of fine motor coordination, such as the beamwalk and gridwalk tests 10,18,19 ; however tests of locomotor ability and exploration in novel chambers show that the mice are not impaired in their ability to walk given that their locomotion distance in a novel arena remains similar to sham mice. 10 The literature surrounding the use of CatWalk as a tool to detect motor impairments after TBI has both negative and positive findings.…”
Section: Discussionmentioning
confidence: 99%
“…The full procedure and application to a mouse model of TBI has been published previously by our group [33]. This test requires no swimming, capitalizes on the natural tendency of mice to avoid open areas in favor of hugging the edges of an apparatus (thigmotaxis), and has been used successfully to distinguish TBI from sham mice previously [33,34]. The RWT maze consists of a 32-inch galvanized steel tub with 9 holes placed at equal intervals around the device, roughly 1½ inch above the apparatus floor.…”
Section: Radial Water Tread Maze (Rwt)mentioning
confidence: 99%
“…Mice were tested at ten days after final impact for spatial memory impairment using a radial water tread (RWT) maze, which was developed specifically to test spatial memory in mice [33,37]. A two-way ANOVA (Days 1-12, between and within subjects factors, respectively) indicated that there was not a statistically significant difference between sham-saline versus sham-paclitaxel mice for either testing day, or the acquisition phase (F[1, 6] = 0.010, p ≤ 0.922, n.s).…”
Section: Spatial Memory Impairment From Repeat Mild Impacts Is Prevenmentioning
confidence: 99%
“…This resilience test requires the integration of a memory test, for example the radial water tread maze, which detects changes in hippocampal function [12][13][14]. In this task, mice are introduced into an approximately 30 in.…”
Section: Sleep Deprivationmentioning
confidence: 99%